CULTURAL LITERACY THROUGH DOCUMENTARY FILM: THE BRAHMAN CEREMONY AS A MEDIUM FOR CULTURAL INHERITANCE - I Nyoman Payuyasa; I Made Denny Chrisna Putra; Ida Bagus Hari Kayana Putra (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Film can reflect the civilization of a country or nation. Through film works, one can clearly see the series of history, culture, philosophy, phenomena, and even social upheavals that have occurred from one era to another. Films, especially documentary films, also serve as powerful media for preserving cultural existence. The role of film in this era of globalization becomes an interesting study to present entertainment that can also serve as guidance for society. Especially considering the current situation of society living amidst the currents of global culture, which undoubtedly threatens the cultural heritage. The purpose of this research is to analyze the values of cultural literacy and the usefulness of the documentary film